Immediate and long-term effects of polysaccharides-based formulations on human skin - Flavio Bueno de Camargo Junior; Lorena Rigo Gaspar; Patrícia Maria Berardo Gonçalves Maia Campos (Universidade de São Paulo, 2012)
A new trend in cosmetic formulations is the use of biotechnological raw materials as the polysaccharides from Klebsiella pneumoniae, which are supposed to enhance cell renewal, improve skin hydration and micro-relief. Botanical extracts of Myrtus communis leaves contain different sugars, which may provide the same benefits. Thus, the objective of this study was to evaluate through objective and subjective analysis the immediate and long-term effects of cosmetic formulations containing polysaccharides biotechnologically-originated and / or the ones contained in Myrtus communis extracts. Three polysaccharide-based and placebo formulations were applied on the forearm skin of 40 volunteers. Skin hydration, transepidermal water loss (TEWL), viscoelasticity and skin micro-relief measurements were made before and 2 hours after a single application and after 15 and 30 day-periods of daily applications. Answers to a questionnaire about perceptions of formulation cosmetic features constituted the subjective analysis. All polysaccharide-based formulations enhanced skin hydration. Formulations with isolated or combined active substances improved skin barrier function as compared to placebo, in the short and long term studies. Formulations containing Myrtus communis extracts had the highest acceptance. Results suggest that daily use of formulations containing these substances is important for protection of the skin barrier function. Uma nova tendência em formulações cosméticas é a utilização de matérias-primas biotecnológicas como os polissacarídeos de Klebsiella pneumoniae, que pode aumentar a renovação celular e melhor a hidratação e micro-relevo da pele. Por outro lado, o extrato vegetal de Myrtus communis contém diferentes polissacarídeos, que também podem proporcionar benefícios à pele. Assim, o objetivo do estudo foi a avaliação dos efeitos imediatos e em longo prazo, de formulações cosméticas contendo polissacarídeos obtidos por processo biotecnológico e/ou de extrato de M. communis por meio de análises objetivas e subjetivas. Três formulações contendo os polissacarídeos e um placebo foram aplicadas na pele dos antebraços de 40 voluntários. As medidas foram realizadas antes e após 2 horas da aplicação das formulações e após 15 e 30 dias de aplicações diárias em termos de hidratação da pele, perda transepidérmica de água (TEWL), viscoelasticidade e micro-relevo da pele. Para a análise subjetiva, os voluntários responderam um questionário a fim de obter-se informações sobre a percepção relativa à qualidade de cosméticos. Todas as formulações provocaram aumento da hidratação cutânea. As formulações que continham os polissacarídeos melhoraram a função barreira da pele, em curto e em longo prazo. A formulação contendo extrato de M. communis apresentou maior aceitação. Os resultados sugerem que o uso diário dos polissacarídeos avaliados é importante na proteção da função barreira da pele.